2010
DOI: 10.3748/wjg.v16.i13.1639
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic osteodystrophy and liver cirrhosis

Abstract: Hepatic osteodystrophy is an important complication encountered in patients with liver cirrhosis and all patients should be monitored for hepatic osteodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
2
11

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 17 publications
4
46
2
11
Order By: Relevance
“…Many factors have been reported to be involved in the occurrence of HO, but its pathophysiology still remains unclear [6]. Chronic cholestasis (such as in primary biliary cirrhosis) [7], low levels of insulin-like growth factor-1 [8,9], impairment of J Gastrointestin Liver Dis, September 2016 Vol. 25 No 3: 323-329 receptor activator of nuclear factor κappa B ligand (RANKL) and osteoprotegerin system [10], vitamin D deficiency [11,12], low body mass index (BMI) [13], chronic alcoholism [14] and sedentary lifestyle [15] were implicated in HO pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors have been reported to be involved in the occurrence of HO, but its pathophysiology still remains unclear [6]. Chronic cholestasis (such as in primary biliary cirrhosis) [7], low levels of insulin-like growth factor-1 [8,9], impairment of J Gastrointestin Liver Dis, September 2016 Vol. 25 No 3: 323-329 receptor activator of nuclear factor κappa B ligand (RANKL) and osteoprotegerin system [10], vitamin D deficiency [11,12], low body mass index (BMI) [13], chronic alcoholism [14] and sedentary lifestyle [15] were implicated in HO pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Sub sequently, Goral et al (10) reported that lower values of osteocalcin as a marker of bone formation were found in patients with virus B and C liver cirrhosis.…”
Section: Discussionmentioning
confidence: 97%
“…Some authors reported that PTH was increased in liver insufficiency, while others underscored that PTH values were normal or even reduced in this condition. The prevailing opinion is that the changes in PTH concentrations have no significant effect on the development of osteoporosis in cirrhotic patients (10,14,15). Although vitamin D inadequacy is very common with these patients, secondary hyperparathyroidism is rather rare (16).…”
Section: Discussionmentioning
confidence: 99%
“…Ключевые слова: ортотопическая трансплантация печени, остеопороз, маркёры костной резорбции № 1/2013 ОстеОпОрОз и ОстеОпатии оригинальные Статьи остеокластов через редуцирование гормонального контроля над прорезорбтивными (провоспалительными) цитокинами ил-1, ил-6 и фно-альфа [15,25], которые воздействуют на резорбцию кости через систему RANK/RANKL/OPG, явля-ющуюся ключевым регулятором остеокластогенеза и актив-ности остеокластов. оценку состояния резорбции кости в настоящее время осуществляют, главным образом, на осно-вании определения в моче N-телопептида (NTx) или в сыво-ротке крови с-телопепдида (стх) коллагена 1 типа или так называемых β-кросслапов (бкл), отражающих активность остеокластов [10].…”
Section: № 1/2013 остеопороз и остеопатии оригинальные статьиunclassified